Following the in-plane disorder of sodiated hard carbon through operando total scattering. Issue 19 (25th April 2019) - Mathiesen, Jette K.; Väli, Ronald; Härmas, Meelis; Lust, Enn; Fold von Bülow, Jon; Jensen, Kirsten M. Ø.; Norby, Poul
Abstract : Mechanisms of ion insertion in hard carbon and the corresponding structural impact on the graphene layer. Abstract : Successfully enabling a new battery technology, such as sodium-ion batteries, requires a thorough understanding of the functional properties of its building blocks. Knowing how the electrode materials behave upon operation is crucial to gain insight into how the battery technologies can be improved for optimal usage. Here we examine with X-ray total scattering and subsequent pair distribution function (PDF) analysis the structural response of hard carbon upon operation, which has been proposed as a possible electrode material for sodium ion batteries. PDF analysis reveals a clear correlation between the interplane and in-plane interatomic distances and the state of charge. The change in in-plane graphene behaviour corresponds to a reversible charge transfer between sodium and the antibonding orbitals in the upper π band of the graphene sheet, resulting in in-plane elongation and contraction upon cycling. As a result of the introduction of sodium into the structure upon discharge, the hard carbon structure is found to become increasingly disordered resulting in the initial structure not being able to fully recover upon desodiation. The more pronounced structural impact upon sodiation than seen in lithiated hard carbon suggests a larger electron transfer impact on the structure by influencing the π-orbitals of the neighboring, conjugated benzene rings. This means that the electron transfer cannot be described as a local electron transfer contribution as might be the case of lithium, but instead as a more delocalized contribution, in which the local structure of graphene experiences a larger change upon sodiation.